Funkční analýza TbFis1 proteinu u Trypanosomy brucei. - Ťápal, Jiří (Jihočeská univerzita, 2014)
Mitochondrial fission and fusion are important processes because they control mitochondrial distribution and function. Two proteins play essential role in mitochondrial fission, dynamin-related protein (termed DRP), primarily localized into the cytosol and Fission protein (Fis1), integral membrane protein, which is located in outer mitochondrial membrane. These proteins are conserved across eukaryotic tree. Homologues of Fis1 protein, was found in yeast and in mammals respectively, are necessary for targeting DRP to outer mitochondrial membrane for occurring mitochondrial fission. Trypanosoma brucei has single large mitochondria in cell and therefore it is ideally suitable model organism for studying mitochondrial fission, which is important for transmission of one complete mitochondria to each daughter cells during cytokinesis. As TbDRP in T.brucei, was already characterized. We aim to identify Fis1 in T.brucei and describe its function. In our study we identified a putative homologue of Fis1, which we called TbFis1. We made knock-down cell lineages of this gene. Our data shows that in T.brucei the TbFis1 protein is not essential for growth of the parasite as well as we did not observe morphological phenotype. This finding is surprising because a lack of Fis1 protein has strong effect on mitochondrial morphology in yeasts and mammals. So it looks like the function of the protein may differ among organisms.
Functional analysis of TbFis1 protein in Trypanosoma brucei.